An investigation of mathematical models of different dynamics involved in wound healing process - MANISHA JAIN (International Journal of Pharma and Bio Sciences, 2017)
Human is the most significant creature on the earth having various complex biological structures. Skin the foremost and important organ of the body with many different functions has always been a center of attraction for a medical scientist. Almost all the functions of the body are managed by the skin. Any disturbance in the body may cause various disturbances in the body. Therefore any wound and its related problems cannot be ignored. Mathematical models of wound healing play an important role to study various complications in biological phenomenon.Theoretical models and wound healing has a close relation to understand whole phenomena of the healing process and activities involved in. Experiments have their limitations on a human being or live organs. Mathematical Models on the basis of experimental facts and figures are competent to obtain results by changing best possible factors without experimental work. The present paper is a review paper on the work done by the researchers. Various mathematical models for the internal and external factors involved in the healing process are discussed. At the end gaps are discussed briefly.